Acoustic frequency-dependent physical mechanism of sub-MHz ultrasound neurostimulation. (1st December 2022) - Fan, Haixiao; Shimba, Kenta; Ishijima, Ayumu; Sasaoka, Kenya; Takahashi, Tsuyoshi; Saka, Eigo; Chang, Chih-Hsiang; Jimbo, Yasuhiko; Azuma, Takashi; Takagi, Shu
Abstract: Ultrasound allows non-invasive and reversible modulation of neural circuit activity with high spatial resolution. Despite growing interest in clinical applications, the safe and effective use of ultrasound neuromodulation has been limited by a lack of understanding of the physical mechanisms underlying its effects. Here, we demonstrate acoustic frequency-dependent physical effects that underlie ultrasound neuromodulation, where cavitation and radiation forces are the dominant sources of low- and high-frequency stimulation, respectively. We used 39.5 and 500 kHz acoustic frequencies to stimulate cultured neural and glial cells to study acoustic frequency-dependent neural responses. We demonstrate increased evoked responses due to increased cavitation activity at the 39.5 kHz acoustic frequency. In contrast, notable cavitation activity was not detected at 500 kHz despite detection of evoked responses. Our work highlights the dependence of ultrasound neuromodulation on acoustic frequencies, with different physical effects underlying cell responses to low and high sub-MHz acoustic frequency ranges.